Optical Response of Poly (1,4-Phenylene-1,2-Di (P-Phenoxyphenyl) Vinylene) Towards Oxygen Gas - F.S Mehamod; R Daik; M Ahmad (ASEAN Journal on Science and Technology for Development, 2004)
This research involved the synthesis of poly (1,4-phenylene-1,2-di (p-phenoxyphenyl) vinylene), dpop-PDV from di (p-phenoxybenzoyl) benzene compound as the monomer. The potential of the produced polymer as sensing reagent for O2 detection based on fluorescence quenching was studied. Di (p-phenoxybenzoyl) benzene was synthesised via the Friedel-Crafts benzoylationwith terephthaloydichloride and biphenylether as starting materials and anhydrous AlCl3 as the catalyst, while the dpop-PDV was synthesized via the McMurry coupling reaction. The polymerization was carried out in THF with TiCl4 and Zn as the catalyst and reducing agent respectively. Characterization on monomer and polymer had been carried out by using FTIR, GCMS, DSC, TGA, GPC and melting point measurement. Response of the polymer towards oxygen gas was described in terms of fluorescence spectra, repeatability, reproducibility and the response curve. Results obtained showed that the fluorescence intensity decreased upon exposure to O2 gas, indicating that the polymer was responsive to the presence of the O2 gas and the sample was found regenerable by flushing the polymer solution with N2 gas.